ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØºÙ†Ø§Ø¡ ÙˆØ§Ù„ØµÙˆØ± Ø¨Ù…Ø¯Ø±Ø³Ø© Ù†ÙˆØ± Ø§Ù„Ù‚Ø±Ø§Ù† Ù„Ù…ÙÙ†Ø±ÙˆØª Ø§ØªØ´ÙŠÙ‡ - Khuzaimah Alfi Syahrina (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
The aims of the research are to identify the process of using picture and singing method in teaching vocabulary; to identify studentsâ€™ responses toward the use of picture and singing method in teaching vocabulary; and to identify the effectiveness of using picture and singing method in teaching vocabulary at SDIK Nurul Quran. The process of using picture and singing methods was achieved by providing several songs and displaying pictures related to the material to be learned and the teacher avoided to give translation in the studentsâ€™ native language (Bahasa Indonesia). Finally, the test result showed that t-score t= 5.037 was higher than t- table t= 1.684 (0.05) = 99.9% (0.001) which indicated that using picture and singing methods for the first grade â€œAl-Falaqâ€ students of SDIK Nurul Quran was effective Keywords: Singing Method; Picture; Vocabulary